STUDENTS’ PERCEPTION OF USING QUIZIZZ IN LEARNING GRAMMAR AT THE 3rd GRADE STUDENTS OF SMP N 5 REMBANG - Sulastri; Febriani, Lidya; Syahrul (JEE (Journal of English Education), 2022)
This research was aimed to find out students' perception on the use of Quizizz as a media in learning grammar at the 3rd grade students of SMP N 5 Rembang in academic year 2022/2023. The problem of this research was the teacher has applied Quizizz in learning grammar, but some students still get score below the Minimum Criteria of Mastery Learning (KKM) especially in solving grammar exercises. The researcher used descriptive quantitative research to describe the phenomenon of students' perceptions of using Quizizz in learning grammar. The population of this research was all of the students at the 3rd grade students of SMP N 5 Rembang. The sample of this research was 62 of the 3rd grade students who were selected using purposive sampling. This research used closed-questionnaire as the instrument in which respondent has to choose one of several answers presented. To analyses the data, researcher used Likert scale. Based on the results of the study, students' perceptions of using of Quizizz as learning media in grammar can be categorized as good perception with percentage 88,90%.